Disponibilidade hídrica no solo, fotossíntese e evapotranspiração em plantas de feijoeiro - Brandão, Diego (2012)
The aim of this study was to verify the photosynthesis rate, stomatal conductance, leaf transpiration, evapotranspiration of common bean plants (IPR Colibri cultivars) under different levels of water availability. The plants have grown up in two soils from Northeast of Parana State - Distrofic Red Nitosol and Red Latosol. There was a factorial experiment set as 4x2x3 in randomized blocks in greenhouse which was consisted of four levels of water availability (100, 75, 50 and 25%), two soil classes Distrofic Red Nitosol and Red Latosol in vases of 20 kilograms of capacity and three reps. The measurements of photosynthesis rate, stomatal conductance, leaf transpiration were made with Infra Red Gas Analyser (IRGA) and it was observed that they reduced as soil humidity was decreased. From the initial development stage to the pre flowering the values of evapotranspiration to 100, 75, 50, 25% water availability treatments were respectively 5,40, 4,94, 4,62 3,07 mm d-1 to Latosol and 3,80, 3,40, 2,80, 2,12 mm d-1 to Nitosol. The photosynthesis rate to 100% of water availability to plants in Latossolo and Nitossolo were 16,0 and 10,9 µmol m-2 s-1 and plants more developed had the higher rates. Evapotranspiration decreased as water availability was decreased being proportional to plant development. Stomatal conductance was the main factor which controlled photosynthesis and evapotranspiration.